Penerapan Keadilan Restoratif pada Tahap Penuntutan Perkara Penganiayaan di Kejaksaan Negeri Jombang - Aditya Ardiano (Jurnal Hukum Lex Generalis, 2025)
The handling of criminal cases through restorative justice at the Jombang District Attorney's Office reflects a progressive legal approach that focuses on restoring social relations. This research uses an empirical juridical method through interviews and documentation studies. Of the 36 cases of abuse in 2022–2024, 12 were resolved restoratively, with an increase of 8 cases in 2024. The main obstacles include the unpreparedness of the victims, low public understanding, and institutional limitations. Research recommends increasing prosecutorial capacity, establishing a team of facilitators, and comprehensive regulation to strengthen the implementation of restorative justice